2006
DOI: 10.1118/1.2403967
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a high fill factor, indirect detection prototype flat‐panel imager for mammography

Abstract: Empirical and theoretical investigations of the performance of a small-area, high-spatial-resolution, active matrix flat-panel imager, operated under mammographic conditions, is reported. The imager is based on an indirect detection array incorporating a continuous photodiode design, as opposed to the discrete photodiode design employed in conventional flat-panel imagers. Continuous photodiodes offer the prospect of higher fill factors, particularly for arrays with pixel pitches below approximately 100 microm.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
61
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 54 publications
(78 reference statements)
2
61
0
Order By: Relevance
“…This results in a significant reduction in detective quantum efficiency ͑DQE͒ under conditions of low exposure or high spatial frequencies 1 and is particularly pronounced for fluoroscopy 1,2 as well as for applications requiring small pixels, such as mammography and breast tomosynthesis. 3,4 In the case of fluoroscopy, it has been shown that the DQE of AMFPIs is inferior to that of image intensifiers ͑XRIIs͒ at the lower end of the exposure range ͑0.1-1 R͒ 5 -where the limited system gain of AMFPIs results in the additive noise 6 becoming significant relative to x-ray quantum noise.…”
Section: Introductionmentioning
confidence: 99%
“…This results in a significant reduction in detective quantum efficiency ͑DQE͒ under conditions of low exposure or high spatial frequencies 1 and is particularly pronounced for fluoroscopy 1,2 as well as for applications requiring small pixels, such as mammography and breast tomosynthesis. 3,4 In the case of fluoroscopy, it has been shown that the DQE of AMFPIs is inferior to that of image intensifiers ͑XRIIs͒ at the lower end of the exposure range ͑0.1-1 R͒ 5 -where the limited system gain of AMFPIs results in the additive noise 6 becoming significant relative to x-ray quantum noise.…”
Section: Introductionmentioning
confidence: 99%
“…2 Given the low quantum efficiency ͑QE͒ of such detectors at radiotherapy energies ͑ϳ2% at 6 MV͒, the detective quantum efficiency ͑DQE͒ of conventional EPIDs is only ϳ1%, compared to ϳ40% -80% for kV AMFPIs. [3][4][5] The low DQE of conventional EPIDs constrains the practical execution of volumetric imaging techniques, such as MV cone-beam computed tomography ͑CBCT͒ 6-13 and cone-beam digital tomosynthesis ͑CBDT͒. 14,15 These techniques are under examination for providing 3D visualization of soft tissues -information that could help ensure accurate execution of advanced treatment plans for 3D conformal radiotherapy 16 and intensity modulated radiotherapy ͑IMRT͒, 17 in which dose delivery is precisely shaped to the tumor treatment volume.…”
Section: Introductionmentioning
confidence: 99%
“…Those detectors that directly detect MV X rays include a 1D arc array of tungsten cavities filled with high-pressure xenon gas, 21 2D gas chambers formed by microstructured tungsten spacer plates 22 and thick HgI 2 photoconductors. 23 For indirect detection, some of the detectors considered include thick optical fibers detecting Cerenkov radiation, 24 2D polymer matrices filled with Gd 2 O 2 S : Tb phosphor, 25 as well as 1D and 2D crystalline scintillators ͑e.g., CsI:Tl, Bi 4 Ge 3 O 12 , CdWO 4 , and ZnWO 4 ͒, employing the concept of segmentation. [26][27][28][29][30][31][32][33][34] A series of theoretical and empirical studies has been previously reported on 2D segmented crystalline scintillators, which consists of matrices of scintillating crystals separated by septal walls to limit the lateral spread of optical photons.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the detective quantum efficiency ͑DQE͒ for conventional MV AMFPIs is only ϳ1%, 3 which is much lower than that for kilovoltage AMFPIs ͑ϳ40% to 80%͒. [4][5][6] In order to significantly improve portal imaging performance, 7 as well as reduce the dose requirement for MV CBCT imaging, [7][8][9] it is necessary to substantially increase the DQE of MV AMFPIs.…”
Section: Introductionmentioning
confidence: 99%